Utilizing Artificial Intelligence to Enhance English Learning at Muhammadiyah Luwuk University: Potentials and Challenges - Mangendre, Yuliana; Nggolaon, Desriani; Nurlaela, Nurlaela (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Artificial Intelligence, as a part of information technology, is now playing a key role in education. This aligns with the rapid advancement of technology and the goal of developing 21st-century skills that students will need in the future. Therefore, the urgency of this research is underscored by its alignment with the 4th Sustainable Development Goal (SDG), which aims to ensure inclusive, equitable, and quality education while promoting lifelong learning opportunities for all. This study aims to explore the extent of AI technology usage by students in the English learning process at the University of Muhammadiyah Luwuk. This study employs a mixed-methods approach, which involves rigorously studying social and behavioral issues by collecting and analyzing qualitative and quantitative data. The study's findings indicate that most respondents, specifically English education students, are familiar with using AI and frequently incorporate it into their daily lives and learning processes. The AI platforms commonly used by respondents include Perplexity, Turnitin, ChatGPT, Grammarly, Quillbot, Mendeley, and Gamma. Notably, 70% of students positively perceive AI, believing it enhances creativity and innovation. However, 30% of students hold the opposite view. Artificial intelligence technology has the potential to provide both benefits and harm. Therefore, integrating technology into education requires a wise approach to offer maximum benefits without sacrificing students' skills, creativity, and critical thinking development.